Fast-Scan Cyclic Voltammetry (FSCV) Reveals Behaviorally Evoked Dopamine Release by Sugar Feeding in the Adult Drosophila Mushroom Body. - Shin, M.; Venton, B.J. (Angewandte Chemie (International ed. in English), 2022)
Drosophila melanogaster, the fruit fly, is an excellent model organism for studying dopaminergic mechanisms and simple behaviors, but methods to measure dopamine during behavior are needed. Here, we developed fast-scan cyclic voltammetry (FSCV) to track in vivo dopamine during sugar feeding. First, we employed acetylcholine stimulation to evaluate the feasibility of in vivo measurements in an awake fly. Next, we tested sugar feeding by placing sucrose solution near the fly proboscis. In the mushroom body medial tip, 1 pmol acetylcholine and sugar feeding released 0.49±0.04 ?M and 0.31±0.06 ?M dopamine, respectively but sugar-evoked release lasted longer than with acetylcholine. Administering the dopamine transporter inhibitor nisoxetine or D2 receptor antagonist flupentixol significantly increased sugar-evoked dopamine. This study develops FSCV to measure behaviorally evoked release in fly, enabling Drosophila studies of neurochemical control of reward, learning, and memory behaviors.